(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Tetrahydrocurcumin (THC) are polyphenolic compounds with para-hydroxyl functional groups and keto functional groups that participate in antioxidant and chemo preventive action (Sugiyama et al. 1996). THC is a hydrogenation product of curcumin produced by reducing curcumin in an organic solvent using a metal catalyst. Plants play a major role in the introduction of new therapeutic agents and have received much attention as sources of biologically active substances. Pterocarpus marsupium has been used for many years in the treatment of diabetes mellitus. Pterostilbene was found to be one of the active constituents in the extracts of the heartwood of Pterocarpus marsupium. Oxidative stress has been suggested to be a contributory factor in development and complication of diabetes. In the present study, we have investigated the effect of tetrahydrocurcumin (THC), one of the active metabolites of curcumin on antioxidants status in streptozotocin - nicotinamide induced diabetic rats. Oral administration of THC at (80mg/kg body weight) and Pterostilbene (40 mg/kg body weight) of diabetic rats for 45 days resulted in significant reduction in blood glucose and significant increase in plasma insulin levels. In addition, THC and Pterostilbene caused significant increase in the activities of superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, reduced glutathione, vitamin C and vitamin E in liver and kidney of diabetic rats with significant decrease in thiobarbituric acid reactive substances (TBARS) and hydroperoxides formation in liver and kidney, suggesting its role in protection against lipid peroxidation induced membrane damage. The antidiabetic and antioxidant effects of THC are more potent than those of Pterostilbene.